2021
DOI: 10.3389/fonc.2020.537789
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Nomogram for Predicting Survival in Gallbladder Cancer Patients With Recurrence After Surgery

Abstract: BackgroundThe management of gallbladder cancer (GBC) patients with recurrence who need additional therapy or intensive follow-up remains controversial. Therefore, we aim to develop a nomogram to predict survival in GBC patients with recurrence after surgery.MethodsA total of 313 GBC patients with recurrence from our center was identified as a primary cohort, which were randomly divided into a training cohort (N = 209) and an internal validation cohort (N = 104). In addition, 105 patients from other centers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Recently, the nomograph has been extensively used as a prediction approach for oncology, which has been proved to have better predictive ability than conventional TNM classi cation 5 . In the former study 6,7 , the nomogram model showed good discrimination for patients with gallbladder cancer as well. However, to date, there haven't been studies on the nomograph prediction model of gallbladder cancer liver metastasis (GCLM).…”
Section: Introductionmentioning
confidence: 83%
“…Recently, the nomograph has been extensively used as a prediction approach for oncology, which has been proved to have better predictive ability than conventional TNM classi cation 5 . In the former study 6,7 , the nomogram model showed good discrimination for patients with gallbladder cancer as well. However, to date, there haven't been studies on the nomograph prediction model of gallbladder cancer liver metastasis (GCLM).…”
Section: Introductionmentioning
confidence: 83%
“…Even though surgical resection is one of the most effective treatments for GBC, more than 60% of patients suffer from postoperative recurrence within five years. [ 3 ] Furthermore, conventional chemotherapy and radiotherapy are unable to significantly prolong overall survival in patients with advanced GBC. Recently, personalized targeted therapy that focuses on the ubiquitin‐proteasome system has emerged as a promising approach for advanced GBC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, GBC usually develops with insidious onset. More than 50% of patients are already at an advanced stage when the tumor is detected, making radical surgical resection difficult or even impossible ( 3 ), while the recurrence rate after surgery is not low ( 4 ). At present, palliative chemotherapy is usually considered to be the treatment option for unresectable GBC, but shows a significantly worse prognosis compared to resected GBC ( 5 ).…”
Section: Introductionmentioning
confidence: 99%